2007
DOI: 10.1111/j.1365-2427.2007.01740.x
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to assess river restoration success

Abstract: 1. Elaborate restoration attempts are underway worldwide to return human-impacted rivers to more natural conditions. Assessing the outcome of river restoration projects is vital for adaptive management, evaluating project efficiency, optimising future programmes and gaining public acceptance. An important reason why assessment is often omitted is lack of appropriate guidelines. 2. Here we present guidelines for assessing river restoration success. They are based on a total of 49 indicators and 13 specific obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(163 citation statements)
references
References 42 publications
1
159
0
3
Order By: Relevance
“…Woolsey et al (2007) found that fish assemblage structure and composition were similar in embanked and restored reaches and concluded that the restoration of the River Thur failed to meet the objectives of near-natural abundance and diversity of fauna. Weber et al (2009) showed that hydrophysical habitat diversity had been improved by the widening but that the current geomorphological complexity was still considerably impaired at the restored reach in comparison with historical near-natural shoreline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Woolsey et al (2007) found that fish assemblage structure and composition were similar in embanked and restored reaches and concluded that the restoration of the River Thur failed to meet the objectives of near-natural abundance and diversity of fauna. Weber et al (2009) showed that hydrophysical habitat diversity had been improved by the widening but that the current geomorphological complexity was still considerably impaired at the restored reach in comparison with historical near-natural shoreline.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the outcome of these projects is essential for adaptive management, evaluation of project efficiency, optimization of future programs, and gaining public acceptance (Woolsey et al, 2007). However, restoration projects often lack post-restoration monitoring using standardized evaluation methods (with welldefined criteria and indicators), which would increase their cost-efficiency Sudduth et al, 2007;Bernhardt et al, 2005Bernhardt et al, , 2007.…”
Section: B Fournier Et Al: Spatio-temporal Heterogeneity Of Ripariamentioning
confidence: 99%
See 1 more Smart Citation
“…The site was restored in 2002 through riverbed widening from 50 to 150 m. The major banks were stabilized by plantations of willows (Salix viminalis). Further information on this site is given in Woolsey et al [23]. We selected six habitats based on the functional process zones (FPZ) [24] proposed by Samaritani et al [25] to represent the different post-restoration successional stages present at the site.…”
Section: Study Areamentioning
confidence: 99%
“…To evaluate the success of floodplain restoration, a reference state to be reached by river restoration has to be determined [26] and a value assessment could be established by using reliable indicators of restoration evaluation. The most frequently used indicators to evaluate the success of river restoration aiming to increase biodiversity are based on vegetation and aquatic fauna [27]. So far, little is known about earthworms as bioindicators of restoration success.…”
Section: Introductionmentioning
confidence: 99%